PRESSURE SENSING USING PHASE MODULATION ON POLYMER[PMMA] - AL_HILLY, SHATHA; HAJIM, KH.; Hassan, N. (Iraqi Journal of Science, 2024)
The effect of pressure, applied to PMMA sample, on Mach -Zender interferencepattern has been studied.The effects of length, depth and height of the PMMA samples on the resultingnumber of fringes are investigated. The results of the experiments show almost alinear behavior between the numbers of displaced fringes and the displacement ofthe PMMA molecules with the applied pressure in all cases.Finally, comparing the experimental with the theoretical results, it is found that,there is a good agreement, in most cases, between them provided introducing acorrection factor which is found to be equal approximately 3.This effect can be usedas a pressure sensor.